Magic Carpet Walls - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes wall murals, a growing trend. Discusses how to affordably paint one's own wall mural and provides tips and tricks for painting. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Mural painting and decoration; Interior decoration